Nearshore Turbid-Zone Corals Exhibit High Bleaching Tolerance on the Great Barrier Reef Following the 2016 Ocean Warming Event - Morgan, Kyle M.; Perry, Chris T.; Johnson, Jamie A.; Smithers, Scott G. (Frontiers in Marine Science, 2017)
High sea surface temperatures (SSTs) on the Great Barrier Reef (GBR) during summer 2015/2016 caused extensive coral bleaching, with aerial and in-water surveys confirming high (but variable) bleaching-related coral mortality. In contrast, bleaching impacts on nearshore turbid-zone reefs, traditionally considered more “marginal” coral habitats, remain poorly documented. This is because rapid ecological surveys are difficult in these turbid water settings, and baseline coral community data from which to quantify disturbance are rare. However, models suggest that the extreme environmental conditions characteristic of nearshore settings (e.g., fluctuating turbidity, light and temperature) may acclimate corals to the thermal anomalies associated with bleaching on offshore reefs, although validation by field evidence has to-date been sparse. Here we present a novel pre- (June 2013/2014) and post-warming (August 2016) assessment of turbid-zone coral communities and examine the response of corals to prolonged and acute heat stress within the Paluma Shoals reef complex, located on the central GBR. Our analysis of 2,288 still video frames (~1,200 m2) which include 11,374 coral colonies (24 coral genera) suggest a high tolerance of turbid-zone corals to bleaching, with no significant changes in coral cover (pre: 48 ± 20%; post: 55 ± 26%) or coral community structure (e.g., Acropora, Montipora, Turbinaria, Porites) following the warming event. Indeed, only one coral colony (Lobophyllia sp.) exhibited full colony bleaching, and just 1.5% of colonies displayed partial pigmentation loss (<20% colony surface). Taxa-specific responses to this thermal stress event contrast with clear-water assessments, as Acropora corals which are normally reported as highly susceptible to bleaching on clear-water reefs were least impacted at Paluma Shoals, a phenomena that has been observed within other turbid settings. Importantly, field surveys confirm regional SSTs were sufficiently high to induce coral bleaching (i.e., comparable number of degree heating days in nearshore and offshore areas), but bleaching severity was much higher at central GBR offshore sites. A more optimistic outlook than is generally offered for nearshore reefs on the central GBR may be implied by our results, which highlights the importance of these resilient but often overlooked coral reef habitats as potential refugia during climate-related disturbances.